An analysis of visitors' behavioral patterns and models of interactive museums in Penang / Muhammad Ammar Maliki - Maliki, Muhammad Ammar (2022)
Penang is a notorious state among Malaysians and overseas travelers with a wide range of attractions, well-known for its delightful cuisines and it is also recognized among the world's leading destinations. Nevertheless, numerous civilians including Malaysians do not know that Penang is a state with the prevalent number of interactive museums in Malaysia. Interactive museums in Penang are able to attract a great figure of visitors including domestic and foreign visitors, while at the same time raising the local economic and living standards. Among the most prominent interactive museums in Penang and frequently visited by tourists are the Muzium & Galeri Tuanku Fauziah (MGTF) and the Penang House of Music (PHM) throughout this study, MGTF and PHM will be applied. This case study provides the diverse type of models employed by interactive museums in Penang and analyze the visitors' behavior pattern at MGTF, as well as PHM in terms of case studies and interactive models. Interactive museums can be considered as one of the methods to entice more tourists in visiting a motherland and also boost the nation's income through a leisure industry. It would be an immense disgrace for MGTF and PHM to experience the absences of visitation from mutually local and foreign visitors, meanwhile numerous parts in the interactive museum have been in better quality and advanced to attract visitors to pay a visit, of which has become one of the landmarks in Penang. This study was also conducted to identify the types of interactive models employed by most of the interactive museums in Penang and how the visitors' behavior patterns at MGTF and PHM determine the relevance of interactive models in both museums. This case study was carried out through information gathered from the primary and secondary data. For instance, the statistics were acquired from the observations, interviews and questionnaire survey as well as available resources such as books, online journals and articles. The researcher's expectation is that this dissertation is able to produce valuable findings that give advantages